The Role of Non-Credit Service in Bank Performance: Empirical Evidence in Vietnam - Hieu, Nguyen Van; Minh, Do Nguyen Nguyet (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 2 No 4, 2022)
This paper examines the impact of non-credit services on Vietnamese bank performance from 2008 to 2017. The research investigates the impact of microeconomic factors, including non-interest service, capital ratio, overheads, loan assets, deposit assets, bank size, and number of ATMs. The empirical results suggest that the size of banks, non-credit services, deposit assets and overheads have been found to have a significant effect on bank performance. Moreover, our results demonstrate that income derived from non-credit services positively and significantly impacts bank performance estimated by Return on Assets (ROA) and Return on Equity (ROE). The study will address endogeneity issues through the Generalized Method of Moments (GMM) and the Two-stage least square method. Our results highlight the importance of income diversification to optimize banks’ operational efficiency in the coming years. The study also explains the positive effect of non-credit services on bank performance. Bank service contributes to the diversification of a bank’s products and services, thereby attracting more customers and retaining customers. Moreover, the development of non-credit products also increases a bank’s position and disperses risks for the bank.